Correlates of poor medication adherence in chronic psychotic disorders. Issue 1 (28th December 2020) - Sajatovic, Martha; Mbwambo, Jessie; Lema, Isaac; Blixen, Carol; Aebi, Michelle E.; Wilson, Betsy; Njiro, Godwin; Burant, Christopher J.; Cassidy, Kristin A.; Levin, Jennifer B.; Kaaya, Sylvia
Abstract : Background: Chronic psychotic disorders (CPDs) occur worldwide and cause significant burden. Poor medication adherence is pervasive, but has not been well studied in sub-Saharan Africa. Aims: This cross-sectional survey of 100 poorly adherent Tanzanian patients with CPD characterised clinical features associated with poor adherence. Method: Descriptive statistics characterised demographic and clinical variables, including barriers to adherence, adherence behaviours and attitudes, and psychiatric symptoms. Measures included the Tablets Routine Questionnaire, Drug Attitudes Inventory, the Brief Psychiatric Rating Scale, the Clinical Global Impressions scale, the Alcohol Use Disorders Identification Test and Alcohol, Smoking and Substance Involvement Screening Test. The relationship between adherence and other clinical variables was evaluated. Results: Mean age was 35.7 years (s.d. 8.8), 61% were male and 80% had schizophrenia, with a mean age at onset of 22.4 (s.d. 7.6) years. Mean proportion of missed CPD medication was 64%. One in ten had alcohol dependence. Most individuals had multiple adherence barriers. Most clinical variables were not significantly associated with the Tablets Routine Questionnaire; however, in-patients with CPD were more likely to have worse adherence ( P ≤ 0.01), as were individuals with worse medication attitudes (Drug Attitudes Inventory, P < 0.01), higher CPD symptom severity levels (Brief Psychiatric Rating Scale, P < 0.001) and higher-risk use of alcohol (Alcohol Use Disorders Identification Test, P < 0.001). Conclusions: Poorly adherent patients had multiple barriers to adherence, including poor attitudes toward medication and treatment, high illness acuity and substance use comorbidity. Treatments need to address adherence barriers, and consider family supports and challenges from an intergenerational perspective.